Recent family research in Sociološki pregled / Sociological review - contribution to the strengthening of the discipline - Čikić, Jovana M; Bilinović Rajačić, Ana Lj (Sociološki pregled, 2018)
The paper analyzes 72 texts relevant to the sociological study of the family, published in the Sociološki pregled/ Sociological Review journal in the period between 2000 and 2017. The analysis includes a quantitative overview of the dynamics of work publishing, characteristics of authorship, representation of topics relevant to the sociological analysis of the family, as well as a qualitative overview of the research context. Special attention is given to papers analyzing the relationship of the family and related concepts (kinship, marriage, reproduction, gender, generations, parenthood), as well as those which focus on the impact of macro social processes and changes on aspects of family functioning. The concusion presents fndings on development tendencies within the discipline, as well as the characteristics of sociological study of the family in Serbia.
Keywords: family; sociology of the family; Sociološki pregled/Sociological review; marriage; parenthood